Lesson Planning for Language Teaching - Sharma, Bam Dev (NELTA Bagmati Journal, 2022)
It is universally accepted that effective teaching is the outcome of an effective lesson plan. It is the signpost of teaching learning activities. Lesson plan becomes a blueprint as it consists of content, methodology, objectives, and process through which measurable and achievable objectives can be obtained. Lesson plan, as a means of technique of teaching, cannot only support teachers; it also provides good feedback and systematic growth in the process of teaching and learning. This article highlights a lesson plan as an instrumental objective of teaching; both innovative and worthwhile for teachers, especially in the field of language teaching. Besides the accompanied sample of lesson plan, can give an outline of how a teacher can make lesson plans interactive to engage students in purposeful teaching learning tasks.